Towards an Interdisciplinary Focus on Sound in Ethnobiology Research - Claire C Wright (Ethnobiology Letters, 2017)
Research on perception and ecological knowledge in ethnobiology has primarily focused on sight, in tandem with taste, smell, and touch. Sound, however, has been largely neglected as a topical or methodological focus. This review addresses research in ethnomusicology and soundscape ecology to suggest how attention to sound could open new avenues and add value to ethnoecological research.